2003
DOI: 10.1046/j.1365-2249.2003.02094.x
|View full text |Cite
|
Sign up to set email alerts
|

Silica accelerated systemic autoimmune disease in lupus-prone New Zealand mixed mice

Abstract: SUMMARYThe genetic backgrounds of lupus-prone murine models are a valuable resource for studying the influence of environmental exposure on autoimmune diseases in sensitive populations. Epidemiological studies have shown associations between silica exposure and several autoimmune diseases, including scleroderma and systemic lupus erythematosus. To determine whether silica exposure can exacerbate systemic autoimmunity in genetically predisposed animals, New Zealand mixed mice were intranasally instilled twice w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
105
0
10

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 111 publications
(122 citation statements)
references
References 19 publications
7
105
0
10
Order By: Relevance
“…Regarding premorbid exposure to silica, only in mice (11,25) has there been a close examination of the relevant changes in systemic cytokine and lymphocyte marker profiles in this context. Recognizing that both immune activation and loss of peripheral tolerance to self are necessary for autoimmune phenomena, Pfau et al (25) have hypothesized that apoptosis exposes antigenic epitopes, otherwise nonexposed, that lead to reaction by the innate immune system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding premorbid exposure to silica, only in mice (11,25) has there been a close examination of the relevant changes in systemic cytokine and lymphocyte marker profiles in this context. Recognizing that both immune activation and loss of peripheral tolerance to self are necessary for autoimmune phenomena, Pfau et al (25) have hypothesized that apoptosis exposes antigenic epitopes, otherwise nonexposed, that lead to reaction by the innate immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with silicosis and other individuals highly exposed to silica have been shown to have increased autoantibodies (8,9), immunoglobulins, and immune complexes (10). However, a recent study of lupusprone mice demonstrated a decrease in serum immunoglobulin levels associated with the development of autoimmunity (11), and decreased levels of immunoglobulins were observed in foundry and pottery workers working in their jobs for an average of ϳ15 years (12).…”
Section: Introductionmentioning
confidence: 99%
“…These mice spontaneously develop pathologic hallmarks of SLE between 6 months and 1 year of age (Rudofsky and Lawrence, 1999;Brown et al, 2003). The most characteristic of these traits are the development of anti-ssDNA, anti-dsDNA, anti-histone, anti-nuclear antigen (ANA), and anti-IgG autoantibodies as well as increased levels of circulating immune complexes (Rudofsky and Lawrence, 1999;Brown et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Lupus-prone New Zealand mixed mice provide an appropriate model to assess the effects of environmental agents on the progression of autoimmune diseases such as systemic lupus erythematosus (SLE) in a sensitive population (Rudofsky and Lawrence, 1999;Brown et al, 2003). NZM mice are a moderately lupus-prone strain with reduced disease penetrance, therefore an environmental influence on SLE in these mice would be more readily observed (Rudofsky and Lawrence, 1999;Brown et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation